Population responses of common carp Cyprinus carpio to floods and droughts in the Pampean wetlands of South America - Tomás Maiztegui; Claudio R.M. Baigún; Javier R. Garcia de Souza; Olaf L.F. Weyl; Darío Colautti (NeoBiota, 2019)
Common carp (Cyprinus carpio) is a global invader that exhibits a wide distribution in Argentina, particularly in shallow lakes and wetlands of the Pampean region. The hydrological conditions of these environments are driven by variations in annual precipitation that determine inter annual changes in water levels leading to flood-drought cycles. The present study focused on understanding the C. carpio population responses to annual rainfall regime and long-term flood and drought events in the Ajó wetlands located in the east of the Pampean region. The results of a two-year biological sampling program showed that C. carpio feeding rate, reproduction, condition, and recruitment were associated with the hydrological cycle. Otolith derived age structure of the population and back-calculated recruitment strength revealed that extraordinary flooding events generated strong cohorts while dry years resulted in low recruitment. Its long-life span (maximum 14 years in Ajó) coupled with a high fecundity, and broad diet allows C. carpio to persist in refugia during dry years and capitalize on wet years when inundation of the floodplain enhances recruitment and facilitates spread. Management and control strategies for this invader should therefore incorporate hydrological variability by promoting intensive removal campaigns during dry years when populations are dominated by large fish confined in remnant water-bodies and, during wet years, carp harvest fisheries should be promoted to reduce population density when increased connectivity is likely to facilitate spread.